1972
DOI: 10.1161/01.res.30.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylcholine on Automaticity and Conduction in the Proximal Portion of the His-Purkinje Specialized Conduction System of the Dog

Abstract: Conventional intracellular recordings from the bundle of His and right bundle branch of the canine heart demonstrated that the slope of diastolic depolarization is markedly depressed by superfusion with relatively small concentrations (4-8 jug/ml) of acetylcholine. As the cells become less automatic, take-off potential increases, rise time of phase 0 is reduced, action potential amplitude increases, and conduction proceeds more rapidly.KEY WORDS right bundle branch determinants of conductivity spontaneous phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 28 publications
(13 reference statements)
3
22
1
Order By: Relevance
“…However, there are conflicting data regarding the importance of direct vagal effects in the ventricular myocardium and the HPS. Several studies have shown that vagal stimulation and ACh infusion exert a negative chronotropic effect on His-Purkinje tissues in vitro and in vivo (52,(60)(61)(62)(63). In addition, ventricular refractory periods are shortened in response to atropine in patients pretreated with propranolol, suggesting a direct cholinergic effect in this tissue (64).…”
Section: Autonomic Effects On the Hpsmentioning
confidence: 99%
“…However, there are conflicting data regarding the importance of direct vagal effects in the ventricular myocardium and the HPS. Several studies have shown that vagal stimulation and ACh infusion exert a negative chronotropic effect on His-Purkinje tissues in vitro and in vivo (52,(60)(61)(62)(63). In addition, ventricular refractory periods are shortened in response to atropine in patients pretreated with propranolol, suggesting a direct cholinergic effect in this tissue (64).…”
Section: Autonomic Effects On the Hpsmentioning
confidence: 99%
“…No other consistent effects on action potential characteristics were observed. Studies by other investigators have shown that ACh can increase maximum diastolic potential, 5 ' 6 rate of rise of phase 0, 5 action potential amplitude, 5 ' 6 and conduction velocity. 5 In both of these studies, preparations were used which had lower membrane potentials than those in our study prior to supervision with ACh.…”
Section: Discussionmentioning
confidence: 88%
“…Studies by other investigators have shown that ACh can increase maximum diastolic potential, 5 ' 6 rate of rise of phase 0, 5 action potential amplitude, 5 ' 6 and conduction velocity. 5 In both of these studies, preparations were used which had lower membrane potentials than those in our study prior to supervision with ACh. In reviewing the contents of Table 1, it is apparent that in our study small increases in MDP did occur with ACh; however, these are statistically insignificant.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations